Biodegradable dissolved organic carbon removal during biological filtration on granular actived carbon - Bouillot, P.; Servais, P.; Billen, G.; Levi, Y. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 1992)
In drinking water production, filtration on granular activated carton (GAC) is generally used in order to remove by adsorption the dissolved organic matter. Nevertheless, the adsorption capacity of GAC is rapidly saturated and it is so necessary to regenerate the GAC. An interesting alternate has been applied in some treatment plants. It consists to use GAC filtration without regeneration taking benefit of the activity of the microbial community which colonize the GAC particles (RITTMAN and HUCK, 1989). In fact, this biological filtration offers the advantage to specially remove the biodegradable fraction of the dissolved organic carbon (BDOC), which is responsible for the problem of bacterial growth into the distribution networks.The bacterial nature of the BDOC removal achieved by the biological filtration on GAC has been now clearly demonstrated (SERVAIS et al., 1991) and some important results of the functioning of these filters has been obtained in studies conducted on pilots filters (BOUILLOT et al., 1990; SERVAIS et al., 1992). These studies have for example shown that only a very small part of the bacterial biomass produced in the filter is exported with the outflow.In the present study, biological filtration has been investigated in a full scale treatment line at Choisy-le-Roi in the Parisian suburbs and the results compared with those gained on pilot filters.The working conditions of the three GAC filter studied are presented in table 1 and compared with those of pilot filters used in a previous study conducted al Neuilly-sur-Marne (table 2). The microbial colonization has been followed in two of the liners. If lasted roughly 3 months to reach biological equilibration, it corresponds to a water volume filtrated of 12 500 m3 per m3 of GAC. Efficiency of the removal during this period is presented in figure 2. Progressively, biological processes take turn with adsorption (fig. 1).As already demonstrated by SERVAIS et al. (1992), the efficiency of biological filtration, calculated in percentage of BDOC removal, increases with increasing contact time whatever the filtration velocity could be in the range 2 m/h to 18 m/h (fig. 3). However, the percentage of BDOC, at similar temperature, is higher in the GAC filters at Choisy-le-Roi than at Neuilly-sur-Marne. The fixed bacterial biomass is also higher at Choisy-le-Roi (average 7.5 µgC/cm3) than at Neuilly-sur-Marne (average 2 µC/cm3).Following during two years the functioning of the n° 56 and 38 filters (tables 3, 4 and fig. 5, 7), it seems that the global efficiency of filtration is better in 1990 than in 1989. This can be linked to the greater fluctuations in BDOC in the influent water in 1989 than in 1990, as shown on figure 8. Fluctuations in the quality of the influent water requires a period to reach the equilibrium during which the effluent is charchacterized by a lower quality (fig. 8). This period is longer at low temperature. The mathematical modal based on the kinetics of the basic microbiological processes involved in biological filtration (the CHABROL model) has been previously developed (BILLEN et al., 1992) in order la simulate the performances of the filtration. It can be used to simulate the vertical profiles of BDOC and bacterial biomass in the filters of the Choisy-le-Roi treatment plant, with modifying only one parameter in the model, the average bacterial mortality “kd” (fig. 4). BDOC decreases versus empty bed contact time (EBCT) calculated by the modal are presented on figure 6 for the Choisy-le-Roi and Neuilly-sur-Marne treatment plants and for two temperatures.From a management point of view, the minimum BDOC is reached for contact time between 15 and 20 minutes at Neuilly-sur-Marne, while at Choisy-le-Roi it is rather between 10 and 15 minutes.In conclusion, BDOC measurements and CHABROL modal constitute powerful tools for management and design of biological GAC filters.